Particle orientation and bulk properties of magnetoactive elastomers fabricated with aligned barium hexaferrite. Issue 6 (6th February 2019) - Breznak, Corey; von Lockette, Paris
Abstract: Abstract : This work studied the relationship between embedded particle volume fraction and magnetic particle orientation distribution in aligned 325 mesh barium hexaferrite (BHF) and polydimethylsiloxane (Sylgard 184; Dow Corning) magnetoactive elastomer (MAE) composites. BHF particles were aligned within the elastomer in the out-of-plane direction, as the material cured. Particle orientation distribution was defined herein by observations of the population of directions at which particle magnetizations resided; magnetization coincides with the physical crystallographic c -axis of BHF. The work used results of vibrating sample magnetometry experiments on MAEs with increasing volume concentrations of embedded ferromagnetic particles (10–30 v/v%) to determine changing widths of analytical particle distribution functions used to describe the range of particle orientations. With over 80% confidence, results showed that MAE composites having the intermediate 15 v/v% had the highest degree of magnetic (and thereby physical) alignment as well as magnetic remanence.